Urgency as a predictor of change in emotion dysregulation in adolescents - Fisher-Fox, Lindsey; Whitener, MacKenzie; Wu, Wei; Cyders, Melissa A.; Zapolski, Tamika C. B. (Frontiers in Psychiatry, 2024)
Introduction Adolescence is a key developmental period characterized by increased maladaptive risky behaviors. Two related but distinct constructs, urgency (the tendency to act rashly in response to strong negative or positive emotions) and emotion dysregulation, are important risk factors for engaging in maladaptive risky behaviors. Thus far, research has largely agreed that these two risk factors are highly correlated. However, the causal direction between these constructs is less understood. The goal of the current study is to determine whether urgency predicts emotion dysregulation change among adolescents. Method This project is an analysis of 544 youth (49.8% female, Mage=14.22, SD=0.52). We tested whether urgency at baseline predicts change in emotion dysregulation over a nine-week period, and whether that relationship differs across boys and girls. Results Two multigroup latent change score path analyses found that negative, but not positive, urgency significantly predicted emotion dysregulation change (negative urgency: b= -0.57, p=0.001; positive urgency: b=0.22, p=0.06). There was no evidence of moderation by gender. Discussion This work provides initial evidence of a temporal relationship between higher negative urgency and increased emotion dysregulation. The next step is to determine whether negative urgency imparts risk for maladaptive behaviors through its effect on emotion dysregulation. The long-term goal of this program of research is to design and test interventions to reduce the impact of negative urgency for adolescent risk-taking.